Characteristics of early adopters of end-user online searching in the health professions. - Marshall, J G (1989)
This paper examines end-user, online searching using data from a questionnaire mailed to 150 Canadian health professionals in practice settings. The response rate was 83% (n = 124). The data provide a demographic profile of early adopters of end-user searching in the health care community. Positive correlations with the user's level of implementation of end-user searching were found for the following variables: amount of time spent in research activities, amount of system training received, and use of Medical Subject Headings (MeSH). There was a negative association between the amount of time spent in patient care and implementation level. General practitioners and family physicians had lower implementation levels than physicians in other specialties. Successful implementers were more likely to be computer literate and to place a high value on formal information sources such as books, journals, and libraries. Health professionals using so-called "user-friendly" or menu-based software had lower levels of personal commitment to using online databases, as measured by a combination of continuance of use, willingness to pay personally, type of recommendations made to colleagues, and hardware ownership.